School Counseling In Malaysia. - See, Associate Professor Dr.,Ching Mey (2004)
The 1998 Counselors Act 580 (Akta Kaunselor 580) has certainly changed the counseling scenario in Malaysia. Together with the implementation of a policy that all secondary schools are to have least one counselor since 1996, the situation of counseling in schools have significantly improved. This paper covers the historical development of the school guidance and counseling movement in Malaysia, role and function of the school counselors, the effectiveness of the counseling services, and the future of school counseling.